Abu Dhabi International Petroleum Conference and Exhibition 2012
DOI: 10.2118/160967-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Growth Monitoring in Polymer Injectors- Field Examples

Abstract: The objective of injecting polymer in brown fields is to increase recovery beyond primary and secondary recovery mechanisms. However, generally it is difficult to achieve adequate (viscous) polymer injectivity in depleted sandstone reservoirs without fracturing. Therefore, monitoring fracture propagation is required in order to control vertical conformance and areal sweep and avoid early polymer breakthrough. Different surveillance methods are used to identify the existence and properties of fractures in polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The same polymer at identical concentrations as those mentioned here is presently being injected in the Romanian field. The significant pressure difference observed in the core flood experiments suggests that induced fractures may be created under field settings, as documented in other studies (e.g., Shuaili et al [36], Moe Soe Let et al [37], and Zechner et al [38]). Field applications of polymers have demonstrated that a significant portion of increased oil production is due to flow diversion rather than acceleration along flow paths.…”
Section: Resultssupporting
confidence: 68%
“…The same polymer at identical concentrations as those mentioned here is presently being injected in the Romanian field. The significant pressure difference observed in the core flood experiments suggests that induced fractures may be created under field settings, as documented in other studies (e.g., Shuaili et al [36], Moe Soe Let et al [37], and Zechner et al [38]). Field applications of polymers have demonstrated that a significant portion of increased oil production is due to flow diversion rather than acceleration along flow paths.…”
Section: Resultssupporting
confidence: 68%
“…Finally, Haynes, A. K., Clough, M. D., Fletcher, A. J. P., & Weston, S., (2013) reported that the rate at which fracture growth occurred was unknown. Choudhuri et al, 2013;Choudhuri et al, 2014;Koning and Mentzer, 1988;Shuaili et al, 2012;Thakuria et al, 2013;Zwaan and Valdez, 2015). This field was discovered in 1956 and started commercial production in 1980.…”
Section: Polymer Injection Ratesmentioning
confidence: 99%
“…Generally, pressure increase observed in polymer injectors is associated to mobility reduction (oil bank formation), shear-thickening behavior of the injected polymer solutions (polymer rheology) and possible formation plugging effects due to poor water quality and/or polymer solubility, among others (Glasbergen G., Wever, D., Keijzer, E., & Farajzadeh, R., 2015; Laoroongroj, A., Zechner, M., Clemens, T., & Gringarten, A., 2012;Lin, Qiu & Guo, 2015;Lotfollahi et al, 2015;Shuaili et al, 2012;Van den Hoek et al, 2012). However, the potential impact of the formation of oil:water emulsion in the presence of polymer (i.e.…”
Section: Water Emulsions In the Presence Of Polymersmentioning
confidence: 99%
“…A direct impact on the viscosity of the polymer solution could not be measured. However, because polymer injection occurred under fracturing conditions (Clemens et al 2013), the induced fractures are growing faster for poorer water quality (Suri et al 2011;Zechner et al 2015) as a result of more-extensive plugging of the fracture interfaces by the sludge. Because growing fractures might impact sweep efficiency if they are extensive (van den Hoek 2004), the water quality had to be improved to reduce this risk.…”
Section: Polymer-solution Quality and Stabilitymentioning
confidence: 99%